Trade and economic impacts of destination-based corporate taxes - Martin, Will (International Food Policy Research Institute, 2017)
Current US proposals for destination-based corporate taxes that effectively combine a value-added tax (VAT) and a wage subsidy raise important policy questions for countries considering them, and for their trading partners. This tax/subsidy package would not create trade barriers or export subsidies, and any changes in trade would result from the measures’ distributional consequences or short-run impacts on output. The package would leave business profits and rents untaxed, placing the burden of the tax entirely on consumers, with no offset from exchange rate appreciation. If anything, its introduction could cause a short-run real exchange rate depreciation. A key concern regarding this package is its small, volatile, and vulnerable revenue yield. At current US consumption and labor shares of gross domestic product (GDP), a 20 percent corporate cash-flow tax with a wage subsidy would generate only around 2 percent of GDP in revenues, a result that could be obtained with much less volatility from a 2.8 percent tax without the wage subsidy. Under the tax/subsidy regime, revenues would become negative if consumption and labor shares returned to their historical norms, requiring increases in other taxes. A 20 percent tax would raise consumer prices by up to 27 percent, taking into account state sales taxes, sharply cutting the living standards of people on fixed incomes. The average combined consumption tax rate of 33 percent would be the highest in the world and more than double the world-average VAT rate, creating incentives for avoidance and evasion.